Sounding out the state of Indonesian music - McGraw, Andrew Clay 1974-; Miller, Christopher J. 1969- (Cornell University Press, 2022)
Sounding Out the State of Indonesian Music showcases the breadth and complexity of music in and of Indonesia. By bringing together chapters on the merging of Batak musical preferences and popular music aesthetics; the vernacular cosmopolitanism of a Balinese rock band; the burgeoning underground noise scene; the growing interest in kroncong in the United States; and what is included and excluded on Indonesian media, editors Andrew McGraw and Christopher J. Miller expand the scope of Indonesian music studies. Essays analyzing the perception of decline among gamelan musicians in Central Java; changes in performing arts patronage in Bali; how gamelan communities form between Bali and North America; and reflecting on the "refusion" of American mathcore and Balinese gamelan offer new perspectives on more familiar topics.Sounding Out the State of Indonesian Music offers a call for a new paradigm in popular music studies, a grappling with the imperative to decolonialize, and recognition of our field's grounding in diverse forms of practice.
Keywords: Anthropology; Asian Studies; Musical Arts & Ethnomusicology; HISTORY / Asia / Southeast Asia; Music -- Social aspects -- Indonesia; Music -- Indonesia -- History and criticism; Musical groups -- Indonesia; Performing arts -- Indonesia; Musikleben; Unterhaltungsmusik; Volksmusik; Indonesien; Konferenzschrift -- 29.03.2018-31.03.2018